2020
DOI: 10.1177/0284185120911187
|View full text |Cite
|
Sign up to set email alerts
|

Stent performance in palliative transhepatic treatment of malignant biliary obstruction: a randomized study comparing covered versus uncovered stents

Abstract: Background Considering the limitations in both uncovered self-expandable metallic stents (USEMS) and covered self-expandable metallic stents (CSEMS), it is difficult to make a general recommendation for their application in percutaneous decompression of malignant biliary obstruction (MBO). Purpose To compare percutaneous transhepatic CSEMSs versus USEMSs for the palliative treatment of MBO in terms of technical success, clinical success, stent patency, patient survival, complications, and stent dysfunction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…There were 36 studies included with 3502 total subjects analyzing 7 stents, FMS, PMS, UMS, PLS, IRS, ARS, and PXS (Figure 1) (Kaassis et al, 2003;Isayama et al, 2004;Soderlund and Linder, 2006;Krokidis et al, 2010;Kullman et al, 2010;Telford et al, 2010;Krokidis et al, 2011;Song et al, 2011;Chen et al, 2012;Sangchan et al, 2012;Zhu et al, 2012;Kitano et al, 2013;Moses et al, 2013;Mukai et al, 2013;Ung et al, 2013;Hu et al, 2014;Lee et al, 2014;Walter, 2014;Yang et al, 2015;Lee et al, 2016;Hasimu et al, 2017;Jang et al, 2017;Jiao et al, 2017;Bernon et al, 2018;Chen et al, 2018;Conio et al, 2018;Jang et al, 2018;Zhu et al, 2018;Hamada et al, 2019;Yuan et al, 2019;Cho et al, 2020;Dhondt et al, 2020;Elkilany et al, 2020;Sakai et al, 2021;Tamura et al, 2021;Wang et al, 2021). There were 7 pair comparisons can be made, such as ARS vs FMS, ARS vs PLS, ARS vs UMS, FMS vs PLS, FMS vs UMS, IRS vs UMS, PLS vs PMS, PLS vs UMS, PMS vs UMS, PXS vs UMS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 36 studies included with 3502 total subjects analyzing 7 stents, FMS, PMS, UMS, PLS, IRS, ARS, and PXS (Figure 1) (Kaassis et al, 2003;Isayama et al, 2004;Soderlund and Linder, 2006;Krokidis et al, 2010;Kullman et al, 2010;Telford et al, 2010;Krokidis et al, 2011;Song et al, 2011;Chen et al, 2012;Sangchan et al, 2012;Zhu et al, 2012;Kitano et al, 2013;Moses et al, 2013;Mukai et al, 2013;Ung et al, 2013;Hu et al, 2014;Lee et al, 2014;Walter, 2014;Yang et al, 2015;Lee et al, 2016;Hasimu et al, 2017;Jang et al, 2017;Jiao et al, 2017;Bernon et al, 2018;Chen et al, 2018;Conio et al, 2018;Jang et al, 2018;Zhu et al, 2018;Hamada et al, 2019;Yuan et al, 2019;Cho et al, 2020;Dhondt et al, 2020;Elkilany et al, 2020;Sakai et al, 2021;Tamura et al, 2021;Wang et al, 2021). There were 7 pair comparisons can be made, such as ARS vs FMS, ARS vs PLS, ARS vs UMS, FMS vs PLS, FMS vs UMS, IRS vs UMS, PLS vs PMS, PLS vs UMS, PMS vs UMS, PXS vs UMS.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies showed the significant 30-day mortality risk compared to others. The highest risk of 30-day mortality were found in ARS, PLS, Linder, 2006; Krokidis et al, 2010;Kullman et al, 2010;Telford et al, 2010;Song et al, 2011;Chen et al, 2012;Sangchan et al, 2012;Zhu et al, 2012;Kitano et al, 2013;Moses et al, 2013;Mukai et al, 2013;Ung et al, 2013;Hu et al, 2014;Lee et al, 2014;Walter, 2014 33.19) in the rate of 30-day mortality than UMS (Figure 6) (Isayama et al, 2004;Sangchan et al, 2012;Zhu et al, 2012;Hu et al, 2014;Lee et al, 2016;Dhondt et al, 2020;Elkilany et al, 2020).…”
Section: -Day Mortalitymentioning
confidence: 93%
See 2 more Smart Citations
“…Three reports have asserted that the patency period of CSEMSs is superior to that of USEMSs[ 4 - 6 ]. However, others have found that the patency period is similar between CSEMSs and USEMSs[ 7 - 9 ]. Although CSEMS insertion has some disadvantages (such as cholecystitis, pancreatitis, and migration), the stent can be removed[ 7 , 10 - 13 ].…”
Section: Introductionmentioning
confidence: 99%